Controlling Cytokine Storm Is Vital in COVID-19 - Tang, Lu; Yin, Zhinan; Hu, Yu; Mei, Heng (Frontiers in Immunology, 2020)
Corona Virus Disease 2019 (COVID-19) has caused a global outbreak and severely posed threat to people's health and social stability. Mounting evidence suggests that immunopathological changes, including diminished lymphocytes and elevated cytokines, are important drivers of disease progression and death in coronavirus infections. Cytokine storm not only limits further spread of virus in the body but also induces secondary tissue damage through the secretion of large amounts of active mediators and inflammatory factors. It has been determined that cytokine storm is a major cause of deaths in COVID-19; therefore, in order to reverse the deterioration of severe and critically ill patients from this disease, the cytokine storm has become a key therapeutic target. Although specific mechanisms of the occurrences of cytokine storms in COVID-19 have not been fully illuminated, hyper-activated innate immune responses, and dysregulation of ACE2 (angiotensin converting enzyme 2) expression and its downstream pathways might provide possibilities. Tailored immunoregulatory therapies have been applied to counteract cytokine storms, such as inhibition of cytokines, corticosteroids, blood purification therapy, and mesenchymal stem cell therapy. This review will summarize advances in the research of cytokine storms induced by COVID-19, as well as potential intervention strategies to control cytokine storms.